How to make 100 ribbon embellishments : trims, rosettes, sculptures, and baubles for fashion, decor, and crafts /: trims, rosettes, sculptures, and baubles for fashion, decor, and crafts. ([2014]) - Schmidt, Elaine, 1950-
No abstract available